Evaluation of the Implementation of the Discovery Learning Model in Learning Mathematics in Deaf Special Junior High Schools - Gst Ayu Mahayukti; Putu Kartika Dewi (Indonesian Journal Of Educational Research and Review, 2022)
Learning mathematics at SMPLB is similar to normal schools in general. The difference is only in the substance of the material and the way the teacher teaches the material in class, where the interaction is carried out using sign language, hand gestures, and emphasis on lip movements which is called total communication. This study analyzed the effectiveness of implementing the discovery learning model in learning mathematics in deaf special schools (SLB). This research is included in the type of evaluation study research. The sample of this study was a mathematics teacher and deaf SMPLB students in grades seven and eight who were taken using a cluster random sampling technique. The number of teachers involved is 3, and the number of students is 18—data collection methods used in questionnaires, interviews, and documentation. The data analysis technique used is quantitative descriptive using the Z-score formula. The results showed that implementing the discovery learning model in learning mathematics in SMPLB for deaf students was classified as less effective. The context variable had a positive score, the input score was negative, the process variable had a negative score, and the product variable had a negative score. The teacher is classified as effective, the context is positive, the input is positive, the process is negative, and the product is positive. The study findings showed that there were as many Z scores with positive signs as negative ones, so the results were equal to zero. Then a positive score was given because Z was closer to the positive score. It happened because the number of research samples was even. Evaluation of implementing the discovery learning model in learning mathematics during a pandemic at SMPLB B for teachers showed that the results were classified as effective.